Exploring a degradation strategy for biogenic amines based on the Cantonese soy sauce production method. (December 2021) - Qi, Qi; Huang, Jun; Zhou, Rongqing; Yang, Menglu; Zhang, Lin; Peng, Can; Jin, Yao; Wu, Chongde
Abstract: Biogenic amines (BAs) and ethyl carbamate (EC) are of great concern to society as potential endogenous hazards produced during traditional fermented food processing. In this work, whether the change in microbial community diversity in Cantonese soy sauce resulted in the differences in BA and EC contents was investigated. BAs, especially phenethylamine, tyramine, and histamine, were positively correlated with Lactobacillus and Weissella, while EC was positively related to Staphylococcus . The results indicated that BA and EC share metabolic pathways, in which the putrescine precursor ornithine is converted into citrulline and then reacts with ethanol to form EC. The ability of Bacillus isolated from the moromi to produce BA was strongest during the middle phase of the process. The contents of BAs involved in histamine were reduced by 66.42% and 69.31% by inoculating Zygosaccharomyces rouxii QH-17 and Tetragenococcus halophilus CGMCC3792, respectively. The contents of BAs were significantly reduced by coculturing T. halophilus CGMCC3792 with Z. rouxii QH-17 once the moromi was polluted during the koji manufacturing process or the initial phase of moromi preparation. The results show that one of the effective strategies for decreasing BAs in the soy sauce process is a biodisturbance strategy based on the functional microbiota. Highlights: Revealing the relationship of dominant genus with BA or EC for Cantonese soy sauce. Confirmed Bacillus has BA-production ability by the BA-screening medium. Identified later-phase moromi resulted in significantly increasing of BA by Bacillus. Developing an approach decreasing the content of BA by biodisturbing.